Persepsi Siswa terhadap Penggunaan Media Pembelajaran Video Animasi dalam Proses Pembelajaran di SMAN 18 Medan - Gracelino Prasetyo Nainggolan; Mario Purba; Nazwa Aulia; Yohanna Sitanggang; Revita Yuni (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to explore students' perceptions of the use of animated video media in the learning process at SMAN 18 Medan. Animation-based instructional media are believed to enhance students' interest, understanding, and motivation, particularly when dealing with abstract material. This research employs a descriptive qualitative method by distributing questionnaires to students who have participated in learning sessions utilizing animated videos. The data were analyzed thematically. The findings indicate that students have a positive perception of the use of animated videos, as they help facilitate easier comprehension of the material, increase concentration, and make the learning process more engaging. However, some students still prefer direct instruction from the teacher. Therefore, it is recommended to combine animated video media with traditional teaching methods to create a more effective learning process that accommodates diverse student learning styles.